Space‐Time Inconsistencies in the Dynamics of Water Coverage: Tracking Walking Floods - Paula Torre Zaffaroni; Javier Houspanossian; Carlos M. Di Bella; Esteban G. Jobbágy (Geophysical Research Letters, 2023)
Abstract Floods in ideal landscapes follow a coherent pattern where single water‐covered areas expand and afterward recede following the inverse sequence, but deviate in real landscapes due to natural or human factors resulting in water coverage shifts. Using remote sensing, we introduced two indices to describe the discrepancies between spatially integrated versus pixel‐level frequency distributions under maximum inundated conditions (dext) and throughout all flooding conditions (dtot), expressed as the relative weight of shifts on each landscape's maximum registered coverage, theoretically ranging between no displacement (<20%) to maximum displacement (≪inf). Globally, over 36 years inundations exhibited redistributions representing, on average, 25% and 45% of their peak extents revealing previously unnoticed extra engaged areas and rotational movements within events, rising up to 500% in meandering rivers (South America) and irrigated croplands (Central Asia). We also assessed the influence of natural and human variables and discussed the indices' potential for advancing flood research.